Biochemical, antioxidants, and mineral constituents of stingless bee honey - Pote, Chandrashekhar L.; Shirsat, Dhananjay V.; Mahadule, Payal A.; Gade, Komal A.; Pandit, Trupti R.; Soumia, P. S.; Thangasamy, Arunachalam; Kumar, Satish; Mahajan, Vijay; Karuppaiah, Vadivelu (Frontiers in Sustainable Food Systems, 2025)
IntroductionFloral honey has gained attention for its host-specific phytochemicals, which are associated with various health benefits, such as wound healing, reducing inflammation, and offering antioxidant protection. Stingless bee honey, in particular is renowned for its medicinal benefits.MethodsThis study compares the pH, electrical conductivity (EC), moisture content, total protein, antioxidant activity, sugar content, and mineral composition of four floral honey samples from the stingless bee, Tetragonula iridipennis and an Italian bee, Apis mellifera.ResultsThe pH of T. iridipennis honey ranged from 3.36 to 3.46, lower than A. mellifera honey (4.48). The EC of T. iridipennis honey (1.01–1.13 mS/cm) was higher than A. mellifera honey (0.58 mS/cm), indicating a greater mineral content. Additionally, T. iridipennis honey showed higher moisture content (16.53–19.79%), protein (825–1184.33 μg/g), antioxidant activity (323.05–353.47 mg/100 g), and mineral concentrations.DiscussionThis study compares the physicochemical and mineral components of T. iridipennis and A. mellifera honey. Significant correlations were found between pH and key components, with T. iridipennis honey showing superior nutritional and medicinal value due to its higher biochemical and mineral composition.